OPTIMAZING THE ROLE OF BHABINKAMTIBMAS TROUGHT BINLUH ACTIVITIES IN PREVENTING DRUGS ABUSE IN PEKALONGAN CITY POLICE STATION - MUHAMMAD DIMAS PERMADI .S (Advances in Police Science Research Journal, 2022)
The rise of drug abuse cases that occurred resulted in the emergence of a sense of concern by the people of Pekalongan City about the impact. The police, through Bhabinkamtibmas, have made efforts to prevent this problem. However, in carrying out its duties, factors were found that indicated obstacles and shortcomings so that the implementation of the Bhabinkamtibmas role was said to be not optimal. This study aims to describe the implementation of the role of Bhabinkamtibmas and describe efforts to optimize the role of Bhabinkamtibmas through binluh activities in preventing drug abuse at the Pekalongan City Police. This research method uses a qualitative approach with the type of descriptive analysis research. The concepts and theories used are crime prevention theory, SWOT analysis theory, and management theory as well as drug abuse concept, optimization concept, Bhabinkamtibmas concepts, and counseling guidance concept. The factual condition based on the results of the research is that in the implementation of the Bhabinkamtibmas role an activity plan was found that did not include efforts to prevent drug abuse to the community, there was one area that was rarely visited by Bhabinkamtibmas, and the reporting process was not as expected. In addition, the ability of Bhabinkamtibmas in providing guidance and counseling tens to be boring and aborts obligations without being oriented to the output of creating community empowerment. The problem-solving effort provided are by increasing the level of community education through counseling in each school, socializing regulations on drug abuse, and empowering the community through the Tangguh village program. Furthermore, maximizing planning in accordance with applicable regulations, dividing the area of counseling guidance, and supervising and providing rewards and punishments to members of Bhabinkamtibmas.